Efektivitas Model Pembelajaran Teams Games Tournament (Tgt) untuk Meningkatkan Interaksi Belajar Siswa Kelas X Pada Mata Pelajaran Al-Qur’an Hadis - Afifah Usmawati; Putriana Kaya Ilmi; Masrikah (CV. Kalimasada Group, 2025)
This study aims to assess the implementation of the teams Games Tournament (TGT) learning model in improving student learning interaction in Al-Qur'an Hadith subjects in Class X Ma Hashimiyah academic year 2024/2025. The approach used is qualitative with descriptive design. Data were collected through observation, interview, and documentation, then analyzed interactively through reduction, presentation, and conclusion. The results showed that the application of the TGT model was able to improve student learning interaction individually and in groups, creating an active, collaborative, and fun learning atmosphere through educational games and competitive tournaments. This Model also motivates students to understand the material of Al-Qur'an Hadith in more depth and strengthen social relationships. Supporting factors for success include the role of teachers, learning media, and student enthusiasm, while the obstacles are time constraints and differences in student abilities. Thus, the TGT model is effective in improving student interaction and learning outcomes.